2023
DOI: 10.1038/s41598-023-33918-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the phosphotransferase system in Parageobacillus thermoglucosidasius

Abstract: Parageobacillus thermoglucosidasius is a thermophilic bacterium characterized by rapid growth, low nutrient requirements, and amenability to genetic manipulation. These characteristics along with its ability to ferment a broad range of carbohydrates make P. thermoglucosidasius a potential workhorse in whole-cell biocatalysis. The phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS) catalyzes the transport and phosphorylation of carbohydrates and sugar derivatives in bacteria, making it important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In addition, functional prediction analysis of microbes showed that there were statistical differences in the activities of starch and sucrose metabolism, phosphotransferase system, ABC transporters, microbial metabolism in diverse environments, and quorum sensing pathways between cluster 1 and cluster 2. A previous study reported that the phosphotransferase system could catalyze the transport and phosphorylation of carbohydrates in bacteria ( Bidart et al, 2023 ); ABC transporters were the key carriers of carbohydrate transport and metabolism ( Chandravanshi et al, 2019 ); and quorum sensing was a cell density-dependent gene regulation system that played an important role in carbohydrate metabolism ( Zeng et al, 2021 ). All results of the present study suggest that Chelativorans, Devosia, Halomonas , and Oceanicaulis might affect the semen quality of drakes by regulating carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional prediction analysis of microbes showed that there were statistical differences in the activities of starch and sucrose metabolism, phosphotransferase system, ABC transporters, microbial metabolism in diverse environments, and quorum sensing pathways between cluster 1 and cluster 2. A previous study reported that the phosphotransferase system could catalyze the transport and phosphorylation of carbohydrates in bacteria ( Bidart et al, 2023 ); ABC transporters were the key carriers of carbohydrate transport and metabolism ( Chandravanshi et al, 2019 ); and quorum sensing was a cell density-dependent gene regulation system that played an important role in carbohydrate metabolism ( Zeng et al, 2021 ). All results of the present study suggest that Chelativorans, Devosia, Halomonas , and Oceanicaulis might affect the semen quality of drakes by regulating carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In P. thermoglucosidasius , deletions of PTS components confirmed PTS-dependent translocation of common lignocellulosic sugars (cellobiose, fructose, glucose, mannose, sucrose, and trehalose) (Bidart et al., 2023 ). Deletion of Enzyme I in a ∆ ptsI strain eliminated growth on these sugars, while normal growth persisted on maltose and xylose thereby indicating alternative transport mechanisms (Bidart et al., 2023 ). Although the ∆ ptsI strain maintained xylose growth, subsequent deletion of xylose-specific EIIB abolished growth on xylose, revealing the continued dependence on facilitated diffusion catalyzed by the xylose-specific enzyme II despite the absence of phosphorylation (Bidart et al., 2023 ).…”
Section: Sugar Transport In Thermophilesmentioning
confidence: 93%
“…PTS transporters have been studied in two thermophiles: Parageobacillus thermoglucosidasius and Thermoanaerobacter saccharolyticum (Tsakraklides et al., 2012 ; Bidart et al., 2023 ). In P. thermoglucosidasius , deletions of PTS components confirmed PTS-dependent translocation of common lignocellulosic sugars (cellobiose, fructose, glucose, mannose, sucrose, and trehalose) (Bidart et al., 2023 ).…”
Section: Sugar Transport In Thermophilesmentioning
confidence: 99%
See 2 more Smart Citations